Caracterização dos efeitos cardíacos produzidos pelo aumento crônico dos níveis cerebrais de angiotensina - (1-7) em ratos hipertensos que superexpressam renina [TGR(mRen2)27] - Lucas Miranda Kangussu Gomes Oliveira (2014)
The renin-angiotensin system (RAS) is a complex hormonal system composed by several enzymes, peptides and receptors. Ang-(1-7) is one of the biologically active peptides of RAS. Chronic intracerebroventricular (ICV) infusion of Ang-(1-7) attenuates arterial hypertension and improves barroreflex control of heart rate. Some initial studies investigated the participation of Ang-(1-7) in the physiopathology of hypertension in transgenic rats that over express tissue renin [TGR(mRen2)27], however, the cardiac effect mediated by Ang-(1-7)/Mas receptor in nervous central system is not well established. The aim of the present study was to characterize the cardiac effects induced by chronic effect of chronic ICV infusion of Ang-(1-7) in TGR(mRen2)27. Sprague-Dawley (SD) and TGR(mRen2)27 rats, with 10 to 12 weeks of age, were divided in four experimental groups: SD subjected to chronic ICV infusion of saline (14 days), hypertensive rats subjected to chronic ICV infusion of saline (14 days), hypertensive rats subjected to chronic ICV infusion of Ang-(1-7) (0,2 g/ h for 14 days) and hypertensive rats subjected to chronic ICV infusion of Ang-(1-7) (0,2 g/ h for 14 days) associated with A779 (1 g/ h for 14 days). It was evaluated: cardiovascular parameters by telemetry, the sensitivity of the barorreflex control of heart rate, cardiac morphology and systolic and diastolic ventricular function by echocardiography, histopathological analysis of left ventricle, determination of the levels of markers of cardiac stress and cellular proliferation by immunoenzymatic assay, evaluation of collagen, fibronectin and RAS components levels by quantitative RT-PCR, measurement of RAS enzymes, ACE and ACE2 activity, determination of RAS peptides levels by radioimmunoassay, evaluation of protein expression of AT1 and Mas receptors by Western blotting and measurement of cardiac autonomic tonus by pharmacologic blockade. We showed that chronic ICV infusion of Ang-(1-7) in TGR(mRen2)27 rats leads to reduction in blood pressure, anti-hypertrophic effects in cardiomyocytes, improvement of barorreflex sensitivity, attenuation of cardiac hyperdinamism, reduction in cardiac levels of ANP, BNP and TGF-β, reduction in collagen type 1 and fibronectin levels, that reflects in cardiac remodeling attenuation and alteration in cardiac RAS components (decrease in ACE expression and activity and increased in ACE2 expression and activity, as well as, reduction in Ang II levels). Finally, we showed that these effects might be associated to alteration in the cardiac autonomic tonus, since rats that received Ang-(1-7) showed restoration of its balance. All the effects induced by Ang-(1-7) wereprevented or attenuated by the concomitant infusion with the receptor Mas antagonist, A779. Altogether, the results of the present study show that activation of the Ang-(1-7)/ Mas axis in the CNS lowers blood pressure and attenuates the cardiac alterations induced by arterial hypertension, which may constitute an important additional strategy for the treatment of cardiovascular diseases.